2010
DOI: 10.1111/j.1468-0432.2009.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Gendered, Invisible Work in Non‐profit Social Service Organizations: Implications for Worker Health and Safety

Abstract: Nonprofit organizations (NPOs) play an important role in the provision of health and social services. In Canada the nonprofit sector includes 7.5 million volunteers and employs over 1.6 million paid workers. The sector is overwhelmingly female-dominated -women make up over 80 per cent of workers in these nonprofit services. Work performed by women has traditionally been undervalued and invisible. It has often been considered safe by researchers, employers, policymakers and sometimes even workers themselves. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 18 publications
0
65
1
Order By: Relevance
“…Such organizations have a complex relationship with governments in liberal market economies because NGOs deliver community and social services on government's behalf, are minimally funded (through fee subsidies) and regulated, and can actively oppose government policies in the pursuit of policy change (Baulderstone, 2007;Brennan, 2008a;Kosny & MacEachen, 2009;Morgan, 2005;Power, 2007;Purcal & Fisher, 2006; United Nations Children's Fund (UNICEF) Innocenti Research Centre, 2008). As a result, NGOs face considerable challenges in continuing to operate.…”
Section: For-and Not-for-profit Services: Funding Issues For Non-governmentioning
confidence: 99%
See 1 more Smart Citation
“…Such organizations have a complex relationship with governments in liberal market economies because NGOs deliver community and social services on government's behalf, are minimally funded (through fee subsidies) and regulated, and can actively oppose government policies in the pursuit of policy change (Baulderstone, 2007;Brennan, 2008a;Kosny & MacEachen, 2009;Morgan, 2005;Power, 2007;Purcal & Fisher, 2006; United Nations Children's Fund (UNICEF) Innocenti Research Centre, 2008). As a result, NGOs face considerable challenges in continuing to operate.…”
Section: For-and Not-for-profit Services: Funding Issues For Non-governmentioning
confidence: 99%
“…These 'invisible workings' leave much of the EC educators' daily work to be taken for granted both by policymakers and communities outside of the LDC service and by the families, children and staff within them. Research suggests that such care work is invisible because it is seen as closely resembling the work traditionally performed by women in the home and is, therefore, of little interest to legislative systems and policymakers (Kosny & MacEachen, 2009). EC educators have consequently reported that they have insufficient influence on the decision-making affecting their daily work practices 7 (Lyons, 1997;Strober et al, 1995;Wolf & Walsh, 1998), and with little input into their LDC services, believe that their current work conditions do not prioritize quality provisions (Carson, Maher, & King, 2007;Fenech, Sumsion, Robertson, & Goodfellow, 2008).…”
mentioning
confidence: 99%
“…Canadian researchers have argued that organizational changes that aim to improve efficiency, which is a topical issue in the Swedish health care context, involve an increase in the invisible work performed by women (Kosny andMacEachen 2010, Messing 1998). Invisible work is often taken for granted and, due to its very nature, not formalized as a value when it comes to job qualifications, with the result that wages are not set accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Invisible work is often taken for granted and, due to its very nature, not formalized as a value when it comes to job qualifications, with the result that wages are not set accordingly. In addition to the question of formalizing work tasks, invisible care work brings with it work environment risks that are not necessarily visible to the naked eye (Kosny andMacEachen 2010, Messing andde Grosbois 2001). One criticism expressed in research is that the invisible work, which is usually carried out by women, has historically been considered safe and without risk because these tasks fall within the realm of the nonvisual (Kosny and MacEachen 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation